A Magyar-Horvát Szabadhajózási Rt. története és tengeri áruforgalma 1900-1914 között = The maritime trade history of the Hungarian-Croatian free navigation company limited between 1900 and 1914 - Pelles, Márton (Közép-Európai Közlemények, 2018)
My study focuses on the story of the Hungarian-Croatian Free Navigation Shipping Company Limited (Magyar–Horvát Szabadhajózási Rt. or Ugarsko-Hrvatsko Dioničarsko Družtvo za Slobodnu Plovidbu) which was founded in 1900 by Sigismondo Copaitich and croatian shareholders as their second steamship company after the Copaitich & Co. (1895). The company was founded so that Croats would also have a long-distance shipping company, beside the Hungaian and the local Italian companies. During the last period of the Dualism, the company mainly connected England’s, the Mediterranean Sea's and the Black Sea's ports, but sometimes the steam ships had also important shippings to the Far East, North and South America. In my paper I would like to present the company’s and Copaitich’s work according to my research and findings in Rijeka's State Archives (Državni Arhiv u Rijeci). From my work I hope that by analysing the company's shipping and goods turnover I can add to an deepen our knowledge about the Hungarian and Croat naval commerce.